Cellulose‐Nanofiber‐Enabled 3D Printing of a Carbon‐Nanotube Microfiber Network. Issue 10 (18th September 2017) - Li, Yuanyuan; Zhu, Hongli; Wang, Yibo; Ray, Upamanyu; Zhu, Shuze; Dai, Jiaqi; Chen, Chaoji; Fu, Kun; Jang, Soo‐Hwan; Henderson, Doug; Li, Teng; Hu, Liangbing
Abstract: Highly conductive and mechanically strong microfibers are attractive in energy storage, thermal management, and wearable electronics. Here, a highly conductive and strong carbon nanotube/nanofibrillated cellulose (CNT–NFC) composite microfiber is developed via a fast and scalable 3D‐printing method. CNTs are successfully dispersed in an aqueous solution using 2, 2, 6, 6‐tetramethylpiperidinyl‐1‐oxyl (TEMPO) oxidated NFCs, resulting in a mixture solution with an obvious shear‐thinning property. Both NFC and CNT fibers inside the all‐fiber‐based microfibers are well aligned, which helps to improve the interaction and percolation between these two building blocks, leading to a combination of high mechanical strength (247 ± 5 MPa) and electrical conductivity (216.7 ± 10 S cm −1 ). Molecular modeling is applied to offer further insights into the role of CNT–NFC fiber alignment for the excellent mechanical strength. The combination of high electrical conductivity, mechanical strength, and the fast yet scalable 3D‐printing technology positions the CNT–NFC composite microfiber as a promising candidate for wearable electronic devices. Abstract : Highly aligned carbon nanotube/nanofibrillated cellulose (CNT–NFC) composite microfibers are successfully fabricated by a fast and scalable 3D‐printing method. Good alignment of both CNTs and NFCs in the microfiber enables strong interactions between them, which leads to a high mechanical strength of 247 ± 5 MPa and an electrical conductivity of 216.7 S cm −1 of the microfiber, holding great promise for wearable electronics applications.